Cost drivers in primary care of patients with chronic diseases - Tyszko, Piotr (Przewodnik Lekarza/Guide for GPs, 2010)
Cost driver is any activity that causes the change of a cost. Patient care, similarly to production processes and services, can be analyzed with the value chain analysis. Main concept of the chain value analysis is to differentiate chain of subjects, processes and actions. One of the stages of value chain analysis is identification and estimation of cost drivers on any level of the chain: subjects, processes or actions. As the examples of chronic diseases in which analyses like this are taken are: Chronic Obstructive Pulmonary Disease – especially its exacerbations, Diabetes, MS, Chronic Hepatitis B.